2020
DOI: 10.1001/jamanetworkopen.2020.21201
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Social Risk Factors and Interest in Receiving Health Care–Based Social Assistance Among Adult Patients and Adult Caregivers of Pediatric Patients

Abstract: IMPORTANCE Health care organizations are increasingly incorporating social risk screening into patient care. Studies have reported wide variations in patients' interest in receiving health carebased assistance for identified social risks. However, no study to date has examined the factors associated with patients' interest in receiving assistance, including whether interest in receiving assistance varies based on specific patient demographic characteristics. Targeted research on this topic could improve the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 55 publications
3
39
0
Order By: Relevance
“…Similarly, homelessness has decreased overall since 2007, but has increased annually between 2017 and 2019 (79). Efforts to address social needs within health care settings as a strategy to improve overall health among AA specifically has been limited, despite the emphasis on measuring and addressing HRSN among lowincome and other racial/ethnic minority patients (12,27,80). Our findings indicate vulnerability to HRSN among patients in a clinic setting serving AA who are higher-income and privately insured.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, homelessness has decreased overall since 2007, but has increased annually between 2017 and 2019 (79). Efforts to address social needs within health care settings as a strategy to improve overall health among AA specifically has been limited, despite the emphasis on measuring and addressing HRSN among lowincome and other racial/ethnic minority patients (12,27,80). Our findings indicate vulnerability to HRSN among patients in a clinic setting serving AA who are higher-income and privately insured.…”
Section: Discussionmentioning
confidence: 80%
“…and implementation framework literature that relies on assessing context, such as available human capital, technical resources, nancial costs, and any other contextual factors that may not be replicable in a larger study, but that provide information about the authenticity and feasibility of delivering core intervention activities in clinical practice (37)(38)(39). This nding is also re ective in and policy recommendations for SDOH screening practices that identify the exibility of SDOH screening program activities to meet the health system context, including patient and staff needs (40,41).…”
Section: Discussionmentioning
confidence: 99%
“… 5 DeMarchis and colleagues found that interest in receiving social assistance was higher among participants who were asked about their desire for assistance before being screened for social risk. 6 …”
Section: Risk Vs Needmentioning
confidence: 99%